EVALUATING ISLAMIC BUSINESS AND FINANCIAL MANAGEMENT IN PRINTING COMPANY: CASE STUDY KUMPULAN KARANGKRAF, MALAYSIA - Hardiansyah, Hardiansyah; Ahmad Azmy; Didin Hikmah Perkasa; Citra Fitria Damayanti; Monika Balqis Pratiwi; Mardati Riza Putri Fatimah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service research tries to evaluate and socialize the implementation of Islamic business management in the Quran printing business of Kumpulan Karangkraf company, Malaysia. The method we used was descriptive qualitative, with data collection techniques of field observation and interviews with informants from the top management of Kumpulan Karangkraf, Malaysia. Technological disruption, competition, and rising printing costs are some issues we obtained after conducting field visits and talking to top management. In addition, the visit was filled with interactive discussions that allowed the management to share experiences and solutions with Islamic business and finance principles. The main result of this research is implementing Islamic business and finance strategies at Kumpulan Karangkraf. In addition to focusing on key account management, increasing the use of Islamic financial products and services can be more effective in enhancing the importance of Islamic business and economic strategies to improve the competitiveness of their products in the market. The implications of this research can contribute to developing corporate strategies that are more favorable to increasing the use of Islamic financial services, which in turn can increase sales, efficiency, and business blessings.